Formação docente e sua relação com a escola - Maria das Graças Nascimento; Patrícia Cristina Albieri Almeida; Laurizete Ferragut Passos (Universidade do Minho, 2016)
This article brings some re flections arising from the analysis of data from the development of the Institutional Program for Scholarships fo r Initiation in Teaching (PIBID) under the Faculty of Education at a public university in the state of Rio de Janeiro ( Brasil). It seeks to identify the co ntributions of th is program for the establishment of a training model of professional deve lopment focused on the school, through the eyes of students and professio nals involved in them. Emphasis is given to practices and training mod els th at promote the rapprochement between university and school, as well as the construction of professional knowledge about teaching.